Diagnostic Accuracy of Serum Procalcitonin (PCT) as an Early Biomarker of Neonatal Sepsis using Blood Culture as Gold Standard: A Prospective Study - Nabi, Siraj; Iqbal, Muhammad Anjum; Masood, Sidra; Shami, Sadaf Saeed; Ali, Husnain; Hamid, Mohsina (Journal of Neonatal Surgery, 2025)
Background: Although neonatal sepsis can be identified and treated early, blood cultures are still the gold standard and, unfortunately, these traditional methods to diagnose sepsis in newborns stagnate progress with their lengthy processing times and delays in yielding results, leading to increased rates of morbidity and mortality. Recently, there has been a shift towards using PCT as a serum biomarker for identifying sepsis in neonates, and one of the central goals of this study is to assess the accuracy of serum PCT in comparison to blood cultures. Methods: This was a prospective study spanning from January 2024 to September 2024 involving 61 neonates with clinical signs of sepsis. Blood samples were taken before any antibiotics were administered for PCT testing and culture. A PCT level greater than 0.5ng/mL was defined as elevated. Diagnostic accuracy parameters (sensitivity, specificity, predictive values, and area under the ROC curve) were calculated. Results: Out of 61 neonates, 25 (41%) had positive blood cultures. Serum PCT levels were elevated in 23 of these cases. ‘The sensitivity and specificity of PCT were 92.0% and 83.3%, respectively’. ‘The negative predictive value was 93.8%, and the area under the ROC curve was 0.927, indicating high diagnostic performance’. Conclusion: Serum PCT is a reliable and effective early biomarker for neonatal sepsis. Its high sensitivity and negative predictive value make it particularly useful in ruling out infection, thus supporting timely and targeted clinical decision-making.